Reply to Comments on the paper "Petrography and Mineralogy of the white marble and black stone of Göktepe (Muğla, Turkey) used in antiquity: New data for provenance determination" by M. Brilli, M.P. Lapuente Mercadal, F. Giustini and H. Royo Plumed (JAS Reports 2018, 19, 625–642). (April 2020) - Brilli, M.; Lapuente Mercadal, M.P.; Giustini, F.; Royo Plumed, H.
Highlights: Reply to Comments of Attanasio et al. about Sr data from Brilli et al. (2018). Clarifications regarding the origin of these samples have been given. Different sample preparation for ICP analysis can produce different results. Abstract: This is a response to the Comments of Attanasio and co-workers regarding the origin of some samples and the results of strontium concentrations reported in the article of Brilli et al., JAS Reports 2018, 19, 625-642. Attanasio et al. have already published strontium contents analysed in presumably the same samples, obtaining largely different and generally higher values than those reported by Brilli et al. In this reply, clarifications regarding the origin of these samples have been given. We also provide a discussion to indicate that the reason for the discrepancies may be mainly related to the different sample processing procedures before the instrumental analysis.